2020
DOI: 10.1007/s00264-020-04607-9
|View full text |Cite
|
Sign up to set email alerts
|

Why are patients dissatisfied following a total knee replacement? A systematic review

Abstract: Background Although total knee replacement (TKR) is an effective intervention for end-stage arthritis of the knee, a significant number of patients remain dissatisfied following this procedure. Our aim was to identify and assess the factors affecting patient satisfaction following a TKR. Materials and methods In accordance with the PRISMA guidelines, two reviewers searched the online databases for literature describing factors affecting patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 36 publications
0
50
1
1
Order By: Relevance
“…Haynes et al reported that younger patients still do achieve a clinically significant improvement after TKA, even though they tend to have less severe radiographic OA and more severe clinical symptoms than older patients before surgery [ 18 ]. Unlike Scott et al or Nakano et al, we found that BMI had no association with dissatisfaction [ 9 , 30 ]. Therefore, although obesity is a well-known risk factor for knee OA and the risk for both prosthetic joint infection and revision surgery is markedly increased among obese patients, based on this study they seem to be as satisfied with the outcome of TKA as non-obese patients[ 21 , 36 ].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Haynes et al reported that younger patients still do achieve a clinically significant improvement after TKA, even though they tend to have less severe radiographic OA and more severe clinical symptoms than older patients before surgery [ 18 ]. Unlike Scott et al or Nakano et al, we found that BMI had no association with dissatisfaction [ 9 , 30 ]. Therefore, although obesity is a well-known risk factor for knee OA and the risk for both prosthetic joint infection and revision surgery is markedly increased among obese patients, based on this study they seem to be as satisfied with the outcome of TKA as non-obese patients[ 21 , 36 ].…”
Section: Discussioncontrasting
confidence: 90%
“…This finding is supported by Scott et al, who reported that over 50 % of patients with KL 2 OA are dissatisfied after TKA [ 9 ]. A systematic review by Nakano et al assessing dissatisfaction after TKA in patients of all ages had a similar finding as well [ 30 ]. Also Niemeläinen et al found mild radiographic OA to be related to dissatisfaction [ 11 ].…”
Section: Discussionmentioning
confidence: 61%
“…Knee replacement surgery has been shown to improve quality of life for KOA sufferers and is cost effective [ 9 ]. However, not all may benefit from it as unfortunately up to 20% of those undergoing TKA are dissatisfied with the outcome [ 23 , 24 ] due to continued pain, with a further 2–3% experiencing life-altering complications. In our patient cohort, a very low number of adverse events were recorded.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of performing a TKA is to achieve a painless and stable knee joint with a functional range of motion (ROM) [ 2 ]. Patient satisfaction following TKA is influenced by a multitude of factors of which post-operative improvement in range of movement and meeting pre-operative patient expectation are key to achieving successful outcomes [ 3 ]. The 10-year implant survival rate is reported to be 96.1%, and the 20-year implant survival rate is 89.7% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%